2017
DOI: 10.18632/oncotarget.v8i48
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The genetic heterogeneity of acute myeloid leukemia (AML) and the variable responses of individual patients to therapy suggest that different AML genotypes may influence the bone marrow (BM) microenvironment in different ways. We performed gene expression profiling of bone marrow mesenchymal stromal cells (BM-MSC) isolated from normal C57BL/6 mice or mice inoculated with syngeneic murine leukemia cells carrying different human AML genotypes, developed in mice with Trp53 wild-type or null genetic backgrounds. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Elevated levels of b-catenin induced by MSCs contribute to drug resistance and maintenance of FLT3-ITD mut LICs (82,92) through the activation of Wnt signalling, which plays a critical role for AML cell survival. The dependency of FLT3-ITD mut LICs on BM-MSC-derived b-catenin is also corroborated in an independent study where FLT3-ITD mut -driven AML showed higher upregulation of b-catenin in BM-MSCs compared to BM-MSCs derived from mice transplanted with AML1-ETO or MLL-ENL-driven AMLs (93). However, upregulation of b-catenin itself is not unique to FLT3-ITD mut AMLs as elevated b-catenin is also seen in MSCs co-cultured with FLT3-ITD wild-type AMLs (82).…”
Section: Flt3-itdsupporting
confidence: 58%
See 2 more Smart Citations
“…Elevated levels of b-catenin induced by MSCs contribute to drug resistance and maintenance of FLT3-ITD mut LICs (82,92) through the activation of Wnt signalling, which plays a critical role for AML cell survival. The dependency of FLT3-ITD mut LICs on BM-MSC-derived b-catenin is also corroborated in an independent study where FLT3-ITD mut -driven AML showed higher upregulation of b-catenin in BM-MSCs compared to BM-MSCs derived from mice transplanted with AML1-ETO or MLL-ENL-driven AMLs (93). However, upregulation of b-catenin itself is not unique to FLT3-ITD mut AMLs as elevated b-catenin is also seen in MSCs co-cultured with FLT3-ITD wild-type AMLs (82).…”
Section: Flt3-itdsupporting
confidence: 58%
“…Consequently, they inherently neglect the competition between distinguishable subclones (i.e., mutated vs. non-mutated clones), which would better reflect the true biological context of clonal expansion. With a few exceptions (93), these questions may be beyond the scope of the studies mentioned in this review; however, without direct comparisons between clones or models driven by different mutations, it is difficult to discern whether a given interaction with the niche may be mutation specific or common amongst many mutations related to a given disease. Indeed, of the limited head-to-head studies that do characterise oncogenic lesion-specific interaction with the BM, they do provide compelling evidence to suggest that the mutational profile can influence the transformation of the BM niche (93).…”
Section: Studying the Subclones In Isolation And In Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of CLP-induced sepsis, it was reported that sepsis induces CD8+ T cell (memory and naĂŻve) exhaustion which affects host defense ( 45 ). Loss of lymphocytes, particularly through apoptosis and inflammatory modes of cell death is a hallmark of sepsis-induced immunosuppression ( 31 , 46 , 47 ). Lymphocytes have been shown to play critical roles during sepsis ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the challenge in early diagnosis and treatment arises from the inconspicuous symptoms and lack of specificity in early-stage tumors. The current surgery, chemoradiotherapy, targeted therapy, and combined treatment in a variety of ways have greatly improved the therapeutic effect of tumors, however, due to the severe side effects and drug resistance, their efficacy remains unsatisfactory ( 1 , 2 ). Hence, there is an imperative to innovate and develop novel treatments that can overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%